Some New Plant Records to the Flora of Gujarat State, India-IV - Meena, S. L. (Indian Forester, 2013)
The present paper deals with 6 indigenous taxa of Angiosperm belonging to 6 genera and 6 families are reported as addition to the flora of Gujarat state. The paper also envisages brief citation, description, flowering and fruiting time followed by ecological notes.